Pengaruh Profitabilitas, Leverage, Likuiditas, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Sektor Pertanian Yang Terdaftar Di Bursa Efek Indonesia Periode 2016-2020 - Ni Gusti Ayu Agung Aistawani; I Wayan Sudiana; Ni Wayan Alit Erlina Wati (UNHI Press, 2022)
In this research, the researcher wanted to know how the influence of profitability, leverage, liquidity and firm size on firm value. The quantitative research is the type of this research. This study uses the purposive sampling technique, and the population in this study as many as 24 companies producing 54 observational data on financial statements based on sampling criteria. The secondary data from the Indonesia Stock Exchange that used in this study are financial reports and annual reports. Data analysis used classical assumption test, multiple linear regression test, f-test and t-test. The profitability variable used in this study is Return on Assets (ROA). The leverage variable is proxied by the Debt to Equity Ratio (DER). Liquidity variable is proxied using Current Ratio (CR). Company size variable in this study uses the company's total assets. Firm value variable is proxied using Price Book Value (PBV). The results showed that there was a positive and significant effect of leverage and liquidity variables on firm value, but the firm size and profitability variable showed no significant effect on firm value.